2020
DOI: 10.4103/jehp.jehp_421_19
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of school-based mental health programs on mental health among adolescents

Abstract: AIM: This study aimed to investigate the effect of school-based interventions on mental health among adolescents in the southeast of Iran. METHODS: This interventional quasi-experimental study included a total of 420 adolescent girls studying 10 th grade in the public schools of Zahedan, Iran. Data were collected using general health questionnaire-28 questionnaire. After pretest, multidimensional interventions (individual education, group educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Similar to the current study, most studies done in other countries and India point toward a positive shift in psycho-social functioning, often with statistical significance. [ 16 25 26 27 28 29 30 31 32 33 34 ] The perceived increase in the ability to deal with stress and conflicts is significant, as interpersonal separation and disputes are vital precipitants of adolescent suicide. [ 35 ] Parental divorce and emotional lability are found to be shared among households attached to blue-collar jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the current study, most studies done in other countries and India point toward a positive shift in psycho-social functioning, often with statistical significance. [ 16 25 26 27 28 29 30 31 32 33 34 ] The perceived increase in the ability to deal with stress and conflicts is significant, as interpersonal separation and disputes are vital precipitants of adolescent suicide. [ 35 ] Parental divorce and emotional lability are found to be shared among households attached to blue-collar jobs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, giving access on mental health service at school also necessary. A study in Iran found a significant reduction in the prevalence of moderate-to-severe mental health issues among the students in the intervention group compared to the control group(Shahraki-Sanavi et al, 2020). Hence, implementing strategies such as identifying student challenges, fostering parent-teacher collaboration, and seeking guidance from expert counsellors can prove to be efficacious in offering pragmatic and efficient resolutions in this domain.…”
mentioning
confidence: 99%